The Effect of Biochar, Lime, and Compost on The Properties of Acid Sulphate Soil - Juhrian Juhrian; Fadly H. Yusran; Raihani Wahdah; Bambang J. Priatmadi (Center for Journal Management and Publication, 2020)
Making acid sulphate soils as paddy fields is a wise choice because it can prevent the soil from oxidizing which occurs in acidification of the soil. The use of biochar as an amendment to the land has long been known since the discovery of terra preta since 1870 in the Amazon Basin as the Amazon dark earth. Because biochar soil amendments are rich in C-organics, have a buffering capacity and can increase soil acidity, are able to absorb heavy metals, and are able to retain water and nutrients for soil organisms. Meanwhile, lime has also been known as an acid sulphate soil amendment in Rome 2000 years ago to balance the acidity in agricultural land. This has been practiced for centuries until now. Though compost or organic soil can be traced more than 2000 years ago. Soil organic matter (SOM) is formed from the remains of animals and plants. It contains C and many nutrients such as N, P, and K. Based on the description above, the author wants to combine the three ingredients in the review, especially in relation to acid sulphate soils.